Língua brasileira de sinais e língua portuguesa no ensino médio: uma proposta de ensino com foco na língua e cultura surda - Ildebrand, Isaias dos Santos (Universidade do Vale do Rio dos Sinos, 2020)
Brazilian Sign Language (Libras) has been conquering space in Brazilian researches and institutions, contributing to the new meanings that focus on language classes. Being a language of viso-spatial modality (GROSJEAN, 1994a; SWANWICK, 2000; QUADROS; KARNOPP, 2004), its learning has been understood as substantial knowledge through the prescriptions that guide the Education of Brazil (BRASIL, 2018), justifying its importance beyond the deaf schools. These considerations are in dialogue with this Master's thesis, which had as its main goal to present and analyze a teaching proposal focusing on deaf language and culture in the mother-tongue classes of students listening to the 3rd grade of Polytechnic High School. As a methodology, the collaborative action-research legitimized the path for the development of the proposal through a teaching project (PIMENTA, 2005; WELLS, 2009; THIOLLENT, 2011; PESSÔA, 2018) organized in stages, analyzed in the light of the multilanguage (KLEIMAN, 2007; BORTONI-RICARDO et al., 2010; ROJO; MOURA 2012; STREET, 2014) and language studies. (FRANCHI, 1992; GERALDI, 1996; KLEIMAN, 2005; HEATH, 2012; SOARES, 2016). It is revealed that the mother tongue class was a vector to mobilize new ways of involving students in contemporary languages. Reading, signage, and production activities with different language modalities have been provided by the work with Libras, while the experiences of the students and the teacher and their relationships with technology were also mobilized. In this way, the scope of Brazilian Sign Language is broadened, enabling its use in a reality that does not depend on this language. It is assumed, therefore, that through the knowledge and understanding of Brazilian Sign Language and deaf culture, possible ways for interaction between deaf and hearing, inclusive perspectives, inserting Sign Language and deaf culture, as well as resignifying (EITELVEN; FRONZA, 2012) the senses and learning (BAKHTIN, 1979) produced in the language classes at school.
Keywords: Língua(gem) no ensino médio; Proposta de ensino; Multiletramentos; Libras; Língua portuguesa; Language in high school; Teaching proposal; Multilanguage; Brazilian sign language; Brazilian portuguese language; ACCNPQ::Lingüística, Letras e Artes::Lingüística